TINJAUAN YURIDIS KEPASTIAN HUKUM PEMILIKAN RUMAH OLEH ORANG ASING YANG BERKEDUDUKAN DI INDONESIA MENURUT PERATURAN PEMERINTAH NOMOR 103 TAHUN 2015 TENTANG PEMILIKAN RUMAH TEMPAT TINGGAL ATAU HUNIAN ORANG ASING YANG BERKEDUDUKAN DI INDONESIA: TINJAUAN YURIDIS KEPASTIAN HUKUM PEMILIKAN RUMAH OLEH ORANG ASING YANG BERKEDUDUKAN DI INDONESIA MENURUT PERATURAN PEMERINTAH NOMOR 103 TAHUN 2015 TENTANG PEMILIKAN RUMAH TEMPAT TINGGAL ATAU HUNIAN ORANG ASING YANG BERKEDUDUKAN DI INDONESIA - admin, Admin; Moh. Rizki Sapta Gunawan; Kholidazia Elhamzah Fathullah; Muhamad Dluha (JUSTNESS - Jurnal Hukun dan Agama, 2024)
Abstract This research discusses "Juridical Review Of The Legal Certainty Of Home Ownership By Foreign People Residing In Indonesia According To Government Regulation Number 103 Of 2015 Concerning Ownership Of Houses In Which Foreign People Reside In Indonesia". The background to this research emphasizes the issue of land ownership by foreigners, which is often a complicated and confusing topic in the legal realm, because it does not only cover aspects of ownership itself. This research aims to find out and understand the legal certainty of ownership of a residence or residence by foreigners domiciled in Indonesia according to PP No. 103 of 2015. As well as understanding the mechanisms for implementing and enforcing laws regarding home ownership by foreigners as regulated in PP No. 103 of 2015. The research method used is normative law, namely discussing problems using the approach of Law PP Number 103 of 2015. The results of the research state that the mechanism for implementing and enforcing the law regarding home ownership by foreigners is as regulated in PP No. 103 of 2015. And regarding legal certainty of ownership of residential or residential houses by foreigners domiciled in Indonesia according to PP No. 103 of 2015 in accordance with the original Article 21 paragraph (3) of the UUPA which states that foreigners obtain property rights due to inheritance without a will or mixing of assets due to marriage. Keywords : Legal Certainty, Foreign Citizens, Land Ownership